Evaluation of two study demands-resources-based interventions: a randomized controlled trial - Körner, Lorena Sarah; Kortsch, Timo; Rieder, Kerstin; Rigotti, Thomas (Frontiers in Psychology, 2024)
Introduction Higher education students experience significant levels of exhaustion in their studies, yet there are limited evidence-based support programs available. Therefore, this study evaluated a novel intervention approach by testing the effectiveness of two online interventions based on the study demands-resources framework. These interventions aimed to balance demands and resources. Derived from the theoretical assumptions of the framework, we hypothesized that the interventions would increase study and personal resources, engagement, and study crafting, and decrease study demands, exhaustion, and self-undermining. Additionally, we hypothesized that demands and resources would mediate the effects of the intervention on engagement, exhaustion, study crafting, and self-undermining. Methods Conducted as a randomized controlled trial with a waitlist control group (n = 71), the study involved participants in two intervention groups who engaged with the interventions for 2 weeks. Intervention group 1 (n = 64) focused on adapting demands, while intervention group 2 (n = 70) focused on increasing resources. The design allowed for a comparison of the effectiveness of these different approaches. Participants completed questionnaires before and after the intervention, and at a 5-week follow-up. Results Results of the analyses of variance with repeated measures revealed that the interventions had significant positive effects on the personal resource mindfulness, two study crafting strategies, self-undermining, and exhaustion. Notably, intervention group 2 exhibited more positive outcomes. The hypothesized mediation effects through mindfulness were partially supported. Discussion The study demonstrates the considerable potential of interventions based on the study demands-resources framework for higher education institutions in supporting student well-being.